Enhancing Industrial Swine Slaughterhouse Wastewater Treatment: Optimization of Electrocoagulation Technique and Operating Mode - Garcia-Mena, V (Academic Press, 2024)
In this study, industrial swine slaughterhouse effluents were treated by an electrocoagulation process (EC) with aluminum and iron electrodes. Batch and semicontinuous operation were performed. EC tests were carried out in batch operating mode for 2.5 h using fixed current densities (j = 10, 20, and 30 mA cm−2) in sulfate and chloride media. At the laboratory scale, higher TOC removal efficiencies were observed using aluminum electrodes at 20 mA cm−2 without the addition of a supporting electrolyte (82.7%). However, the EC process with Fe electrodes consumed 43.6% less energy. After the best operating parameters were found at the laboratory scale, the process was tested as a semicontinuous prepilot process using a filter-press FM01-LC-type electrochemical reactor equipped with flat plate aluminum electrodes. In this stage, current densities and mean linear flow rates were assessed. The highest TOC removal efficiency of 72.7% (i.e., residual TOC concentration of 85.18 mg L−1) in the semicontinuous process was achieved by the application of j = 25 mA cm−2 and ur = 0.64 cm s−1 with an energy consumption of 19.80 kW h m−3. The residual COD and TP concentrations met the international standard limits. Moreover, complete decoloration and disinfection were accomplished. EDXRF, SEM, EDAX, XRD, and FTIR analyses indicated that pollutants were removed by adsorption on aluminum/iron hydroxides/oxyhydroxides. © 2023 Elsevier Ltd